Getting to the heart of the debate: TQM and middle manager autonomy - Alexandros Psychogios; Adrian Wilkinson; Leslie T Szamosi (2009)
The purpose of this paper is to address the generic research question of the effects of the implementation of Total Quality Management (TQM) on managers’ lives. In particular, this study focuses on TQM effects on middle managers’ (MMs) autonomy. Through a multi-modal research approach based on a combination of quantitative and qualitative methods, it is argued that the implementation of TQM programmes has a positive impact on MMs’ autonomy. Nevertheless, it is related mostly to the ‘hard’ rather than the ‘soft’ side of TQM. The strong impact of TQM practices on MMs’ responses to aspects related to their work, as compared to the small impact of the ‘soft’ side, implies a pragmatic view of TQM. Managers perceive a somewhat linear road to quality improvement through the use of ‘hard’ management practices and giving less importance to concepts, such as empowerment and employee involvement.